2005
DOI: 10.1111/j.1442-2042.2004.00987.x
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal seminoma with ‘burned out’ phenomenon in the testis

Abstract: The rare 'burned out' phenomenon in germ cell tumors is known as the presence of an extragonadal germ cell tumor without traces of neoplasm in the testis. This condition is different and less common from the primary extragonadal germ cell malignancies. These malignancies are treated surgically with or without adjuvant chemotherapy or radiotherapy and their prognosis is better than that of other types of primary extragonadal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 3 publications
1
19
0
3
Order By: Relevance
“…Retroperitoneal seminoma without involvement of the testis is uncommon [1][2][3]. Two to five percent of the malignant germ cell tumors (GCT) are extragonadal in origin [1,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retroperitoneal seminoma without involvement of the testis is uncommon [1][2][3]. Two to five percent of the malignant germ cell tumors (GCT) are extragonadal in origin [1,4].…”
Section: Discussionmentioning
confidence: 99%
“…The burned out tumors of the testis need to be distinguished from true EGGCT because the primary removal of the testicular tumor leads to a satisfactory outcome. These malignancies are treated surgically with or without adjuvant chemotherapy or radiotherapy [1,2]. Seminomatous EGGCT have an equivalent prognosis as their primary gonadal counterpart [1,4].…”
Section: Discussionmentioning
confidence: 99%
“…Often it's difficult for clinicians distinguish primary germ cells tumour to metastatic lesion specially for seminoma, which tend to spread by lymphatic channel to retroperitoneal lymph nodes. Previous reports in literature described a "burned out" phenomenon of germ cells tumours, consisting in extragonadal germ cell tumour with no evidence of neoplasm at the testis level [5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed favourable outcomes both for short and long follow-up periods with combined modality treatment approach and revealing the higher frequency of metastatic retroperitoneal tumours from primary unevolved testicular tumour [5,[18][19][20][21][22][23] (Table 1). …”
Section: Discussionmentioning
confidence: 99%
“…Çeşitli immünolojik veya iskemik mekanizmalar öne sürülse de en olası mekanizmanın immünolojik olduğu düşünülmektedir. Endokrin bir takım bozuklukları olan hastalarda burnedout tümör bildiren yayınlarda endokrin bozuklukların varlığı immünolojik mekanizmalar ile ilişki tutulmuştur (43,44). Saleh ve ark.…”
Section: Tümör Regresyon Patogeneziunclassified